Measures of eHealth literacy: options for the Malaysian population - Arina Anis Azlan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Health literacy is an important component to the self-management of one’s health decisions. As information on the Internet becomes more easily accessible, individuals need to be properly equipped to seek and evaluate the health information available to them. Digital health literacy, or eHealth literacy, refers to an array of skills required to properly seek, access, understand and apply health information on the Internet. To date, a number of different models and instruments have been developed to measure eHealth literacy, including the eHealth Literacy Scale (eHEALS), the eHealth Literacy Framework (eHLF), the Digital Health Literacy Instrument (DHLI), the eHealth Literacy Questionnaire (eHLQ), the eHealth Literacy Assessment Toolkit (eHLA) and the Transactional eHealth Literacy Instrument (TeHLI). While some of these instruments rely on the individual’s self-assessment of eHealth literacy, others also test for functional information, communication and technological competencies. This paper presents these different eHealth literacy instruments and how they have been applied in current research. The similarities and differences between the instruments are examined. The discussion concludes with a summary of the measures and potential ways forward in developing an eHealth Literacy instrument for the Malaysian population. It is hoped that this paper may benefit researchers, health care providers, practitioners, ministries and governing bodies interested in understanding eHealth literacy and its measures.